On Exponential Sums Related to the Circle Problem - Slezeviciene, R.; Steading, J. (Ukrains’kyi Matematychnyi Zhurnal, 2004)
Let r(n) count the number of representations of a positive integer n as a sum of two integer squares. We prove a truncated Voronoi-type formula for the twisted Mobius transform $$\mathop \sum \limits_{n \leqslant x} \;\,r(n)\;\exp \left( {2π i\frac{{nk}}{{4l}}} \right),$$ where k and l are positive integers such that k and 4l are coprime, and give some applications (almost periodicity, limit distribution, an asymptotic mean-square formula, and O- and Ω-estimates for the error term).